Oferta de gastronomía sin gluten en la Cafetería Vintage del cantón Cotacachi - Fuentes Moreno, Tatiana Elizabeth (2024)
The growing demand for gluten-free gastronomic options in tourist destinations such as Cotacachi has prompted the Vintage Garden Cafeteria to innovate in its culinary offerings. The general objective of this project is to develop three gluten-free desserts that meet the needs of gluten-intolerant customers, with the intention of positioning the establishment as an inclusive and competitive gastronomic reference in the region. The specific objectives include identifying the demand for gluten-free products, selecting suitable ingredients and creating recipes that ensure a satisfactory culinary experience. The methodology used combined synthetic, analytical and applied approaches, relying on surveys and tastings to evaluate the acceptance of the new products among customers. As a result, three desserts were developed: quinoa cake with chocolate and nuts, amaranth cheesecake with grapefruit, and rice flour muffins filled with apple and blueberries. These desserts not only meet the requirements of a gluten-free diet, but also offer an innovative and attractive gastronomic experience. Finally, this project not only satisfies a specific food need, but also contributes to local economic development and strengthens the competitiveness of the Vintage Garden Café in the tourism sector. The results obtained provide a solid basis for maintaining and expanding a gluten-free dessert offer that appeals to a wider public.